Rozwój nauk handlowych w Polsce Ludowej — rola i miejsce ośrodka poznańskiego - Kramer, Teodor (Wydział Prawa i Administracji UAM, 1980)
The present state of internal trade sciences in Poland has been shaped by activities of academic scientific centres, research institutes and economic practicians. A substantial contribution to this development is of Poznań centre of commercial sciences, that has been managed by Professor Zbigniew Zakrzewski for 30 years. The Professor's personality, His particular competence for organizing research teams for main scientific problems, also for those ones inspired by life needs, have caused, that He has been gathering around many co-workers and pupils, shaping research visage and style of the Poznań scientific centre The article contains description of basic research directions taken up under Professor's leadership, as well as presentation of the centre contribution to the trade theory, economic thought development in trade sciences, domestic market functioning, consumption economics and population's consumption.
Development of Commercial Sciences in People's Poland — the Place and Role of Poznań